Framing Analysis of the Dynamics of Sexual Violence by Female Santri in Online Media Portals (Case Study Kompas.com Daily News and Republika for July 2022) - Dara Nabila Dianti; Ismi Dwi Astuti N; Prahastiwi Utari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to carry out a framing analysis of news texts contained in online media portals regarding cases of sexual violence that occurred against female students at the Shiddiqiyyah Islamic Boarding School, Jombang. Through descriptive qualitative research methods, researchers try to process existing data in the form of online media portal news using framing analysis formed by the Entmant model. The results obtained an interpretation through framing that Kompas.com tends to focus on the whereabouts of accused perpetrators who committed sexual violence and female students victims who are still experiencing trauma in their lives, while the Republika media portal tends to focus on the existence of the Shiddiqiyyah Jombang Islamic Boarding School which is suspected of actually hindering the process law enforcement if the operating license is not revoked. This illustrates that each editor has its own framing method and cannot be compared